2021
DOI: 10.3892/etm.2021.10607
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine ferulate prevents high‑glucose‑induced filtration barrier injury of glomerular endothelial cells

Abstract: Filtration barrier injury induced by high glucose (HG) levels leads to the development of diabetic nephropathy. The endothelial glycocalyx plays a critical role in glomerular barrier function. In the present study, the effects of piperazine ferulate (PF) on HG-induced filtration barrier injury of glomerular endothelial cells (GEnCs) were investigated and the underlying mechanism was assessed. Immunofluorescence was used to observe the distribution of the glycocalyx as well as the expression levels of syndecan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…AI-AgNPs-treated group except for slight vacuolation and dilation of sinusoids (Figure 8). These results are in line with other mechanisms of interaction of nano Ag with cells that have been presented in the study [90], and various researchers have reported different approaches for diabetic medicine [91][92][93][94][95][96][97]. Considering the results obtained from antidiabetic activity, green-synthesised AgNPs are good anti-diabetic agents.…”
Section: Discussionsupporting
confidence: 87%
“…AI-AgNPs-treated group except for slight vacuolation and dilation of sinusoids (Figure 8). These results are in line with other mechanisms of interaction of nano Ag with cells that have been presented in the study [90], and various researchers have reported different approaches for diabetic medicine [91][92][93][94][95][96][97]. Considering the results obtained from antidiabetic activity, green-synthesised AgNPs are good anti-diabetic agents.…”
Section: Discussionsupporting
confidence: 87%
“…Syndecan-1 is one of the receptors for MDK and has been reported to regulate the expression of TJPs (ZO-1, occludin) [32]. We found that after siRNA interference with Syndecan-1 expression (Fig.…”
Section: Cervical Cancer Cell-derived Mdk Promotes Lnm In Vitro and I...mentioning
confidence: 63%
“…Inflammatory cytokines, like IL-1β and IL-6, can dampen the body’s ability to respond to insulin in fat, muscle, and liver. These cytokines are like pieces of a puzzle that explain how inflammation can lead to IR [ 68 , 69 ]. Prolonged high blood sugar due to IR directly damages blood vessel cells (endothelium, smooth muscle) and immune cells (macrophages), triggering abnormal blood clotting and tissue breakdown.…”
Section: Discussionmentioning
confidence: 99%